Consequences of parental preconceptional irradiation: Endocrine-metabolic pathology in offspring - S. F. Sosnina; P. O. Okatenko; M. E. Sokolnikov (Радиационная гигиена)
Epidemiological studies of late effects of preconceptional (prior to conception) radiation exposure are necessary in order to understand the risks of tumor and non-tumor pathology in next generations. Research of possible relation between parental preconceptional exposure and development of endocrine and metabolic disorders in the offspring is one of the topical issues of radiation hygiene. The objective of the study: comparative analysis of endocrine and metabolic pathology in children of the individuals exposed to long term preconceptional external gamma-radiation at the Mayak Production Association – at the first atomic industry facility on Russia. Materials and methods: A retrospective research was performed based on the Ozyorsk Children’s Health Registry. Ozyorsk – the city where Mayak Production Association is the enterprise forming the city. Analysis of endocrine and metabolic disorders was performed for 13880 children of 1949-1973 years of birth who were born and resided in Ozyorsk; parents of 9321 children of this number had accumulated doses of prolonged external gamma-radiation exposure at the production facility prior to conception. A comparative analysis of the structure and incidence of “Endocrine, nutritional and metabolic diseases” and nosological forms of this class of pathology was performed. Characteristic features of parental preconceptional exposure were analyzed in relation to thyroid pathology in children. Relative risk of endocrine and metabolic disorders among the children of exposed and unexposed parents was calculated for the whole disease class and for certain nosologies. Results: A significant predominance of thyroid diseases, particularly, iodine deficiencies, was detected at an earlier age among the offspring of Mayak Production Association workers compared to the control group; these cases were mostly related to low dose parental preconceptional exposure. Thyroid cancer was further detected in 0.16% (15/9321) of the studied cohort of the offspring of exposed parents with average manifestation age of 42.6. Relative risk of thyroid diseases was significantly higher among the exposed parents’ offspring compared to the controls: 2.0 among boys (95% confidence interval 1.38-2.9), 1.59 among girls (1.25-2.02) and in the group as a whole – 1.64 (1.34- 2.01). Relative risk of thyroid diseases related to iodine deficiency among the offspring of Mayak Production Association personnel was almost twice higher than the in the control group: 1.92 (1.3-2.84) among boys, 1.68 (1.29-2.2) among girls, 1.7 (1.36-2.12) in the whole group. Discussion and conclusion: A statistically significant overweight of non-tumor thyroid pathology in the offspring of Mayak Production Association personnel cannot be explained through external reasons taking into account similar climate and geographic conditions, possible technogenic exposure and the same unified medical survey of the followed children. We cannot exclude increased sensibility if thyroid tissue to iodine deficiency and its predisposition to hypertrophy and hyperplasia among the offspring of individuals exposed to long term occupational contact with ionizing radiation sources; that should be taken into account in the course of medical monitoring of these patients. Further research of transgenerational effects in the offspring of personnel of radiation hazardous production facilities are needed for complete understanding of the role of parental occupational exposure in health risks for further generations.